1979
DOI: 10.1055/s-0028-1085336
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Changes During Intensified Induction-Therapy of Acute Lymphoblastic Leukemia

Abstract: In 49 children with acute lymphoblastic leukemia serial EEGs were performed during the course of treatment. Therapy in the first four weeks consisted of: Prednisone, vincristine, daunorubicine and L-asparaginase. In the second month 6-mercaptopurine, cytosin-arabinoside, cyclophosphamide, methotrexate-i. th. and cranial irradiation were administered. Maintenance-therapy consisted of 6-mercaptopurine, cyclophosphamide and methotrexate i.v. Before treatment only 24% of patients showed normal EEG-findings, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Searching for a correlation between CSF glutamine concentration and the hematological data, we were not able to demonstrate a correlation between CSF glutamine, the WBC, the risk group or the duration of symptoms. Our study revealed significant worsening of the EEG during the induction treatment and near normalization during the subsequent consolidation treatment as has been shown in earlier studies [3][4][5][13][14][15]. However, in this study, the timing of the EEG investigations and the parallel analysis of CSF amino acids make further considerations on the etiology of the EEG changes and the underlying encephalopathy possible.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Searching for a correlation between CSF glutamine concentration and the hematological data, we were not able to demonstrate a correlation between CSF glutamine, the WBC, the risk group or the duration of symptoms. Our study revealed significant worsening of the EEG during the induction treatment and near normalization during the subsequent consolidation treatment as has been shown in earlier studies [3][4][5][13][14][15]. However, in this study, the timing of the EEG investigations and the parallel analysis of CSF amino acids make further considerations on the etiology of the EEG changes and the underlying encephalopathy possible.…”
Section: Discussionsupporting
confidence: 57%
“…Toxic and metabolic effects of VCR and L-ASP have been discussed as the main cause of the EEG-slowing occurring during induction treatment [3,4,14,15]. The most frequent neurological side effect of VCR is peripheral axonal polyneuropathy [22].…”
Section: Discussionmentioning
confidence: 99%
“…The present study joins intentions of a number of reports speculating on the correlation of neurophysiological abnormalities with psychological, neurological and morphological disturbances among clinically asymptomatic long-term survivors of childhood ALL [6,7,9,22]. Primary questions were whether CNS prophylaxis with cranial irradiation prior to or during methotrexate application induced greater neurotoxicity, measured by means of EEG, than treatment regimens with radiotherapy after methotrexate or methotrexate alone, and whether the assessed EEG abnormalities are associated with signs of neurological, morphological or psychological deficits.…”
Section: Discussionmentioning
confidence: 77%
“…Promoted by its importance for the surveillance of cerebral seizures and related CNS disturbances, the investigation of the brain electrical activity by means of neurophysiological techniques developed into one of the favoured instruments for functional CNS screening procedures in clinical practice. For several years, conventional EEG recordings have been widely used for the evaluation of patients with leukemia to assess either the prognosis [5], acute neurotoxic side effects of anticancer treatment [6,7], or to assist in the differential diagnosis of CNS involvement [8,9]. However, its usefulness has not been established for any of these purposes and no conformity exists either about its sensitivity or specificity, or its predictivity for further treatment-related abnormalities in CNS morphology and function.…”
mentioning
confidence: 99%
“…As others [8,9,14,15] we studied the correlation of neurophysiological abnormalities with psychological, neurological and morphological alterations among healthy long-term survivors of childhood ALL. The primary question was whether CNS prophylaxis consisting of CI and ith MTX induced a greater prevalence of neurophysiological abnormalities that the alternative regimen consisting of a combination of MD-MTX and ith MTX.…”
Section: Discussionmentioning
confidence: 99%